Large‐Deviation Principle for Interacting Brownian Motions. Issue 2 (31st March 2016) - Seo, Insuk
Abstract: We prove the large‐deviation principle for the empirical process in a system of locally interacting Brownian motions in the nonequilibrium. Such a phenomenon has been proven only for two lattice systems: the symmetric simple exclusion process and the zero‐range process. Therefore, we have achieved the third result in this context and moreover the first result for the diffusion‐type interacting particle system.© 2016 Wiley Periodicals, Inc.